Empowering STEM Education: Navigating Challenges and Embracing Innovations - Sukmayadi, Dodi (Universitas Terbuka, 2023)
This article exposes the main arguments of each article published in this issue. In Tara Brabazon's article, the focus is on addressing student attrition in universities, advocating for strategies like universal design and the abundance model to support student success. Lineo Lynnette Tool's study in South African universities explores underrepresented groups in STEM leadership, suggesting that targeted efforts can encourage their ascent, using a mixed-methods approach. Asmera Teshome Negeri and Jeilu Oumar's article from Addis Ababa University investigates the gap between engineering graduate skills and employers' needs in Ethiopia, emphasizing the importance of real labor market skills assessments and practical-oriented teaching. Dominic Patric G. Galdonez's research at the Philippine Science High School-Ilocos Region Campus highlights mixed perceptions of research support and strong motivation among teachers for research-related activities. Khut Sokha and Shimizu Kinya's study establishes a framework for teaching science through an integrated STEM approach (ISTEMA), identifying six elements and exploring the integration of science with engineering and technology in primary and lower secondary education. Ethel Reyes-Chua, et.al., from Paranaque City College, delve into metacognitive strategies employed by college students in the Philippines during the pandemic, emphasizing self-motivation and students' resilience. Sunil Dehipawala, et.al., address challenges in teaching measurement uncertainty in physics lab classes during the Covid-19 pandemic, providing insights into experiential learning and assessment rubrics for remote delivery. Prasart Nuangchalerm & Veena Prachagool's paper discusses the integration of AI in STEM education, analyzing transformative potential of AI-driven learning analytics, highlighting the need for ethical considerations in implementing technological innovations.